Magnetic ZnFe2O4-C3N4 Hybrid for Photocatalytic Degradation of Aqueous Organic Pollutants by Visible Light - Yao, Yunjin.; Cai, Y.; Lu, F.; Qin, J.; Wei, F.; Xu, C.; Wang, Shaobin (American Chemical Society, 2014)
Magnetic ZnFe2O4-C3N4 hybrids were successfully synthesized through a simple reflux treatment of ZnFe2O4 nanoparticles (NPs) (ca. 19.1 nm) with graphitic C3N4 sheets in methanol at 90 °C, and characterized by X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric and differential thermal analysis, X-ray photoelectron spectroscopy, high-resolution transmission electron microscopy, and UV-vis diffuse reflectance spectroscopy. Also, the catalytic activities ofheterogeneous ZnFe2O4-C3N4 catalysts were evaluated in photo-Fenton discoloration toward Orange II using H2O2 as an oxidant under visible light (? > 420 nm) irradiation. The reaction kinetics, degradation mechanism, and catalyst stability, as well as the roles of ZnFe2O4 and C3N4 in photoreaction, were comprehensively studied. It was found that the ZnFe2O4-C3N4 photocatalysts presented remarkable catalytic ability at neutral conditions, which is a great advantage over the traditional Fenton system (Fe2+/H2O2). The ZnFe2O4-C3N4 hybrid (mass ratio of ZnFe2O4/g-C3N4 = 2:3) exhibits the highest degradation rate of 0.012 min-1, which is nearly 2.4 times higher than that of the simple mixture of g-C3N4 and ZnFe2O4 NPs. g-C3N4 acted as not only a p-conjugated material for the heterojunction formation with ZnFe2O4, but also a catalyst for the decomposition of H2O2 to ·OH radicals. The heterogeneous ZnFe2O4-C3N4 hybrid exhibited stable performance without losing activity after five successive runs, showing a promising application for the photo-oxidative degradation of organic contaminants.